Drp1-dependent mitochondrial fission regulates p62-mediated autophagy in LPS-induced activated microglial cells. Issue 3 (4th March 2019) - Chae, Unbin; Kim, Han Seop; Lee, Hyun-Shik; Lee, Sang-Rae; Lee, Dong-Seok
ABSTRACT: Microglial activation is known to be an important event during innate immunity, but microglial inflammation is also thought to play a role in the etiology of neurodegenerative diseases. Recently, it was reported that autophagy could influence inflammation and activation of microglia. However, little is known about the regulation of autophagy during microglial activation. In this study, we demonstrated that mitochondrial fission-induced ROS can promote autophagy in microglia. Following LPS-induced autophagy, GFP-LC3 puncta were increased, and this was suppressed by inhibiting mitochondrial fission and mitochondrial ROS. Interestingly, inhibition of mitochondrial fission and mitochondrial ROS also resulted in decreased p62 expression, but Beclin1 and LC3B were unaffected. Taken together, these results indicate that ROS induction due to increased LPS-stimulated mitochondrial fission triggers p62 mediated autophagy in microglial cells. Our findings provide the first important clues towards understanding the correlation between mitochondrial ROS and autophagy. Abbreviations: Drp1; Dynamin related protein 1, LPS; Lipopolysaccharide, ROS; Reactive Oxygen Species, GFP; Green Fluorescent Protein, CNS; Central Nervous System, AD; Alzheimer's Disease, PD; Parkinson's Disease, ALIS; Aggresome-like induced structures, iNOS; inducible nitric oxide synthase, Cox-2; Cyclooxygenase-2, MAPK; Mitogen-activated protein kinase; SODs; Superoxide dismutase, GPXs; Glutathione Peroxidase, Prxs; Peroxiredoxins Graphical abstract: : The mechanistic cascade between LPS-induced mitochondrial fission and autophagy in BV-2 microglial cells.